Evaluation of Knee Cartilage Diurnal, Activity, and BMI-Related Variations Using Quantitative T2 Mapping MRI and Fitbit Activity Tracking - Matcuk, George R., Jr.; Jones, Ian A.; McIntyre, J. Alex; Burt, Robert; Hwang, Darryl; Cen, Steven; Schein, Aaron J.; Vangsness, C. Thomas, Jr. (The Journal of Knee Surgery, 2019)
The aim of this study is to evaluate diurnal variation in knee cartilage 3 Tesla magnetic resonance imaging (MRI) T2 mapping relaxation times, as well as activity- and body mass index (BMI)-dependent variability, using quantitative analysis of T2 values from segmented regions of the weight-bearing articular surfaces of the medial and lateral femoral condyles and tibial plateaus. Ten healthy volunteers' daily activity (steps) were tracked with Fitbit pedometers. Sagittal MRI T2 maps were obtained in the morning and afternoon on days 2 and 3. Mean T2 values were analyzed for variation related to the number of steps taken (activity), time of day (diurnal variation), and BMI using mixed effect model. Significant (albeit small) differences in the medial femoral and medial tibial cartilage regions were identified between morning and afternoon scans (diurnal variation). Daily activity did not result in significant changes and increasing BMI only demonstrated a slight increase in T2 values for the lateral tibial plateau. These findings suggest that it may be necessary to control diurnal variation when using quantitative MRI T2 mapping to assess articular cartilage longitudinally in healthy participants. Further investigation is needed to confirm these findings and determine if they also apply to symptomatic patients.
Keywords: knee cartilage; quantitative T2 mapping; diurnal variation; Fitbit; activity tracking